2021
DOI: 10.2147/jhc.s286213
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Gamma-Glutamyl Transpeptidase to Lymphocyte Count Ratio in the Early Postoperative Recurrence Monitoring and Prognosis Prediction of AFP-Negative Hepatocellular Carcinoma

Abstract: Background: Currently, there is still a lack of effective biomarkers for the recurrence monitoring and survival prognosis assessment of hepatocellular carcinoma (HCC) patients with alpha-fetoprotein (AFP)-negative (≤20 ng/mL) after radical resection. Methods: The clinicopathological data of 606 patients (303 in the AFP-negative group and 303 in the AFP-positive group) who underwent radical resection of HCC were analyzed retrospectively. Results: The gamma-glutamyl transpeptidase to lymphocyte count ratio (GLR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 38 publications
(46 reference statements)
4
15
0
Order By: Relevance
“…Many indicators have been explored or developed to predict the prognosis of patients with HCC. Moreover, we have verified several indexes in our previous work [ 12 14 ]. Since primary liver cancer is considered to be an immunosuppressive tumor so that the indicators that reflect immune response or liver function have always been focused on by researchers [ 15 ].…”
Section: Introductionsupporting
confidence: 80%
“…Many indicators have been explored or developed to predict the prognosis of patients with HCC. Moreover, we have verified several indexes in our previous work [ 12 14 ]. Since primary liver cancer is considered to be an immunosuppressive tumor so that the indicators that reflect immune response or liver function have always been focused on by researchers [ 15 ].…”
Section: Introductionsupporting
confidence: 80%
“…The previous study found that in HCC patients with AFP-negative after radical resection, GLR had fair accuracy in predicting the early-recurrence, and our ndings persisted [13].…”
Section: Declarations Ethical Approval and Consent To Participatesupporting
confidence: 72%
“…Recently, some researchers have proposed that the aspartate aminotransferase to neutrophil ratio index (ANRI), aspartate aminotransferase to platelet ratio index (APRI), platelet to albumin ratio (PAR) and neutrophil times γglutamyl transpeptidase to lymphocyte ratio (NγLR) were independent effective predictors of the prognosis of patients with HCC [8][9][10][11]. Similarly, the preoperative gamma-glutamyl transferase to lymphocyte ratio (GLR) has been found to have signi cant prognostic value after resection in HCC patients with single tumor size ≤ 5 cm and with AFP-negative [12][13][14]. However, the prognostic value of GLR has not been reported in the monitoring of the recurrence of HCC patients with staging I-II following curative resection.…”
Section: Introductionmentioning
confidence: 99%
“…For example, PSA-derived indices, such as free-to-total PSA (F/T) values and prostate-specific antigen density (PSAD), have been found to exhibit greater diagnostic accuracy than PSA alone ( 12 14 ). In addition, several inflammatory and neurotrophic markers, including neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, monocyte-to-lymphocyte ratio ( 15 , 16 ), gamma-glutamyl transpeptidase-to-lymphocyte count ratio ( 17 , 18 ), red cell distribution width-to-platelet ratio ( 19 , 20 ), and alanine transaminase-to-aspartate transaminase ratio ( 21 , 22 ), have previously been shown to have predictive value not only as inflammatory markers but also as indicators for the diagnosis and prognosis of malignancies. To date, studies focusing on the role of these composite indicators in the differential diagnosis of PCa are limited.…”
Section: Introductionmentioning
confidence: 99%